Detached harmonies : a study in/on developing social processes of environmental education in eastern southern Africa - O'Donoghue, Rob B (Rhodes University, Faculty of Education, Department of Education, 1997)
Long-term social processes are explored to examine the shaping of environmental education in eastern southern Africa. The study opens with early Nguni social figurations when 'to conserve was to hunt.' It then examines colonial conservation on the frontiers of imperial expansion and developing struggles for and against wildlife preservation. These processes shaped an inversion of earlier harmonies as declining wildlife was protected in island sanctuaries of natural wilderness and 'to conserve was not to hunt.' Inside protected areas, conservation management struggles shaped new harmonies of interdependence in nature, enabling better steering choices in developing conservation science institutions. Here more reality congruent knowledge also revealed escalating risk which was linked to a lack of awareness amongst communities of 'others' outside. Within continuing conservation struggles, education in, about and for the environment emerged as new institutional processes of social control. The study examines wilderness experience, interpretation, extension, conservancies and the development of an environmental education field centre, a teacher education programme and a school curriculum. Naming and clarifying the emergent education game for reshaping the awareness and behaviour of others is examined within a developing figuration of environmental education specialists. Particular attention is given to academic and statutory processes shaping environmental education as a field of objective principles and rational processes within modernist continuities and discontinuities into the 1990's. An environmental education field centre, an earth-love curriculum and research on reserve neighbour interaction are examined as political sociologies developing within a declining power gradient and wide ranging socio-political change. Into the present, a final window on a local case of water pollution examines shifting relational dynamics revealing how environment and development education models of process may have little resonance amidst long-term socio-historical struggles and shifting controls over surroundings, others and self. A concluding review suggests that grounded critical processes engaging somewhat blind control over surroundings may yet reshape self-control and social control amongst others. The trajectories of these clarifying struggles must remain open-ended as sedimented myth and memory is reshaped within ongoing processes of escalating risk and global intermeshing.
Keywords: Environmental education -- South Africa